Psychiatric disorders and symptoms severity in patients with adenotonsillar hypertrophy before and after adenotonsillectomy - YILDIRIM, YAVUZ SELİM; Soylu, Erkan; Soylu, Nusret; YILDIRIM, YAVUZ SELİM; Sakallioglu, Oner; Polat, Cahit; Orhan, Israfil (My University, 2013)
Objective: The objective of this study was to compare the frequency of psychiatric disorders and the severity of psychiatric symptoms in patients with adenotonsillar hypertrophy with a healthy control group and investigate the potential improvement after adenotonsillectomy.